Cloning and Molecular Analyses of a Gibberellin 20-Oxidase Gene Expressed Specifically in Developing Seeds of Watermelon - Kang, Hong-Gyu (American Society of Plant Physiologists, 1999)
To understand the biosynthesis and functional role of gibberellins (GAs) in developing seeds, we isolated Cv20ox, a cDNA clone from watermelon (Citrullus lanatus) that shows significant amino acid homology with GA 20-oxidases. The complementary DNA clone was expressed in Escherichia coli as a fusion protein, which oxidized GA(12) at C-20 to the C(19) compound GA(9), a precursor of bioactive GAs. RNA-blot analysis showed that the Cv20ox gene was expressed specifically in developing seeds. The gene was strongly expressed in the integument tissues, and it was also expressed weakly in inner seed tissues. In parthenocarpic fruits induced by 1-(2-chloro-4-pyridyl)-3-phenylurea treatment, the expression pattern of Cv20ox did not change, indicating that the GA 20-oxidase gene is expressed primarily in the maternal cells of developing seeds. The promoter of Cv20ox was isolated and fused to the β-glucuronidase (GUS) gene. In a transient expression system, β-glucuronidase staining was detectable only in the integument tissues of developing watermelon seeds.